Women Empowerment in India: Issues and Challenges - Seema Rani (International Journal on Economics, Finance and Sustainable Development, 2021)
This paper attempts to analyze the status of Women Empowerment in India and highlights the Issues and Challenges of Women Empowerment. Women empowerment means emancipation of women from the vicious grips of social, economical, political, caste and gender based discrimination. We can analyze their conditions through a number of parameters like their involvement in household decision making right, freedom of thought, financial authority, gender equality, political participation, media exposure, access to education etc. It is noticed that still gender inequality is a serious concern and is prevailing dominantly in our society. This as an agenda has been on top of the lists of most government plans & programs as well. Efforts have been made on a regular basis across nations to address this issue and enhance the socio-economic status of women. However, it has been observed that most of the policies and programs view empowerment in the economic sense only working in the belief that economic self-reliance empowers women ignoring other variables like health, education, literacy etc.